The enigma of Calonectria species occurring on leaves of Ilex aquifolium in Europe - C. Lechat; P.W. Crous; J.Z. Groenewald (IMA Fungus, 2010)
Species of Calonectria are common saprobes and plant pathogens on a wide range of hosts occurring in subtropical to tropical regions of the world. The aim of the present study was to resolve the status of new Calonectria collections obtained on Ilex leaves from France. Based on DNA sequence data of their β-tubulin and histone gene regions, as well as morphology, the new collections matched the ex-type strain of Cylindrocladium ilicicola. On the host and in culture, yellow to brownish-yellow perithecia were observed that did not strain red in 3 % KOH. Based on these results, C. ilicicola and its purported teleomorph, Ca. pyrochroa, were shown to represent two distinct species, as the latter has bright red perithecia that strain purple in KOH. A new combination, Ca. lauri, based on Tetracytum lauri, is subsequently proposed for C. ilicicola. Calonectria lauri is distinct from Ca. ilicicola, a pathogen commonly associated with Cylindrocladium black rot of peanut. Finally, Ca. canadiana is proposed as new name for Cy. canadiense, which is a nursery pathogen involved with root rot of several tree genera in Quebec, Canada.